Change in Femoral Cartilage Cross-Sectional Area After Aerobic and Resistance Exercise - Lim, Junhyeong; Lee, Jaewook; Park, Sanghyup; Lee, Jinwoo; Kim, Jaewon; Park, Jihong (International Journal of Sports Medicine, 2024)
We compared the immediate response and recovery of femoral cartilage morphology following aerobic or resistance exercise to a control condition. Fifteen healthy young males (23.9 years; 170.1 cm; 69.7 kg) visited the laboratory three separate days and randomly performed one of the 30-min exercise aerobic exercises (treadmill running), resistance exercises (leg presses, back squats, and knee extensions), or seated rest as the control, each followed by the 50-min recovery. Ultrasonographic images of the femoral cartilage cross-sectional area (CSA) were obtained before and after exercise and every 5 min thereafter. To test exercise effects over time, a mixed model analysis of variance and Tukey–Kramer post-hoc tests were performed (p<0.05). The femoral cartilage CSA was different (condition×time: F34,742=4.30, p<0.0001) and the femoral cartilage CSA was decreased after the aerobic (−5.8%, p<0.0001) and the resistance (−3.4%, p=0.04) exercises compared to the pre-exercise levels. Deformed femoral cartilage CSA took 35 and 10 min to return to the pre-exercise levels after aerobic and resistance exercises (p+>+0.09), respectively. Thirty minutes of moderate exertion performing aerobic or resistance exercises immediately reduced the femoral cartilage CSA. A rest period ranging from 10 to 35 min was required for cartilage recovery after weight-bearing exercises.
Keywords: cartilage deformation; ultrasonography; running; weightlifting; blood lactate concentration